Hubungan Pengetahuan dengan Upaya Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Karyawan PT Sambas Wijaya - Catur Bayu Prasetya; Meida Laely Ramdani (Faletehan Health Journal, 2022)
The implemetation of occupational health and safety (OHS) is highly important for employees’ safety, so that the implementation efforts are required. Knowledge about OHS is needed in a company to minimize work accidents due to employee's negligence. This research was to find out the correlation between knowledge and implementation efforts of occupational health and safety (OHS) in the employess of Sambas Wijaya Inc. This study was quantitative and used the cross-sectional approach technique. The samples were 65 employees of Sambas Wijaya Inc. Purbalingga, who were selected by purposive sampling technique. The majority respondents were 33 to 37 years old. The background knowledge of 70.8% of respondents was senior high school graduate. 75% of respondents had been working for more than five years in one of four occupations: crusher, asphalt mixing plant, maintenance, and logistics. The majority of respondents had a high level of OHS knowledge, namely 44 people (67.7%). The implementation of OHS done by most of the respondents was at a good level, namely 39 people (60%). The bivariate analysis used chi-square, showing that there was a significant correlation between knowledge level and implementation efforts of OHS in employees of Sambas Wijaya Inc. with the r-value 12.766 > r table 5.9915 and p-value 0.002 < α 0.0).